Backscatter ratios for nonspherical ice crystals in cirrus clouds calculated by geometrical-optics-integral-equation method. (March 2017) - Masuda, Kazuhiko; Ishimoto, Hiroshi
Abstract: Backscatter ratios for two kinds of ice crystal models, an irregularly shaped Voronoi aggregates (VA) and a regularly shaped hexagonal columns (COL), are calculated using the geometrical-optics-integral-equation (GOIE) method for volume equivalent sphere radii ( R eq ) ranging from 2.8 to 202.0μm. Ice crystals are assumed to be randomly oriented in three-dimensional (3D) space. Characteristics of the depolarization ratio ( δ ) and the lidar ratio ( L ) at a wavelength of 0.532μm and the color ratio ( χ ) at a wavelength pair of 1.064 and 0.532μm are investigated. The backscatter ratios calculated for VA are generally larger than those for COL. For example, L, δ, and χ for VA are approximately 50 60, 0.5 0.6, and 0.8 0.9, respectively, in the range of R eq >10μm; 4 15, 0.2 0.3, and 0.45 0.5 for COL. Effects of deformation of COL on the backscatter ratios are examined by using hexagonal columns with hollowness. It is shown that the L, δ, and χ values significantly increase due to the hollowness. Furthermore, the degree of increase of the backscatter ratios is considerably sensitive to the crystal size and the depth of hollow. On the other hand, backscatter ratios calculated for VA show rather steady values with respect to the number and size of facets. Highlights: Backscatter ratios for ice crystal models are calculated by GOIE method. Hexagonal columns and Voronoi aggregate models are examined. Calculated backscatter ratios are compared with lidar measurements.